A concept for ontology-based value of cybersecurity knowledge - Adiel Aviad; Krzysztof Weçel; Witold Abramowicz (International Journal of Management and Economics, 2018)
This paper focuses on cybersecurity knowledge, claiming that this knowledge may have a value of its own, and suggests a market mechanism to foster the creation of this kind of value. The goal is to elaborate the value of cybersecurity knowledge and propose a semantic approach with an example model to enable better handling of the relevant body of knowledge and its value. The problem of attributing value to cybersecurity should be perceived as analogous to that in information technology. We have examined the relevant body of knowledge with a focus on its characteristics from the viewpoint of different types of market players and their interests. By applying our model, it is possible to increase the accessibility of knowledge and observe externalities from sharing thereof.
Keywords: D46; D62; D89; 650; cybersecurity; threats; value; Semantic Web